P1020ROLE OF CHRONIC KIDNEY DISEASE AND ASSOCIATED BIOCHEMICAL ALTERATION ON ARTERIAL STIFFNESS IN T2 DIABETIC PATIENTS WITHOUT CARDIOVASCULAR DISEASE. (6th June 2020) - Rotondi, Silverio; Tartaglione, Lida; Pasquali, Marzia; Muci, Maria Luisa; Mazzaferro, Sandro; D'onofrio, Luca; Carbone, Angela; Leto, Gaetano; Mignogna, Carmen
Abstract: Background and Aims: DMT2 and its complications such as chronic kidney disease (CKD) lead to increase vascular stiffness, measurable with CAVI, and biochemical alterations in substances implicated in vascular damage like Klotho, FGF23, and Sclerostin. The aim of the study was to evaluate the role of CKD stage 1-2 and possible alterations of 25 (OH)Vitamin-D, FGF23, Klotho, and Sclerostin on early vascular damage in DMT2 patients Method: Patients included: DMT2 from <10 years, age <60 years, no insulin therapy, eGFR≥60 ml/min/1.73m2, absence of vascular complications. We have evaluated CAVI, albumin-excretion-rate (ACR), 25(OH)Vitamin-D, Klotho, FGF23, and Sclerostin. 30 healthy subjects were the control for CAVI, Klotho, FGF23 and Sclerostin. Results: We enrolled 40 women and 60 men, average age 56 years (IQR: 52-59), 5-year DMT2 (IQR: 2.7-7), HbA1c 6.3% (5.8-6.7), eGFR of 95 ml/min/1.73m 2 . FGF23 (42±10 vs controls 29.8±11 pmol/l, p<.05) and Sclerostin (36.2±7 vs 26.6±1 pmol/l, p<.05) were increased and Klotho reduced (673±300 vs 845±330 pg/ml, p<.05). CKD (ACR≥30mg/gr; eGFR between 60-90 ml/min /1.73m 2 ) was present in 12.6%. The mean CAVI value was normal. Patients with borderline (≥8, 33%) and pathological (≥9, 13%) CAVI were older (p.001), with longer duration of DMT2 (p.022) and lower 25(OH)Vitamin-D (p.041). CAVI correlated positively with age (p.001), Hb1Ac (p.036), systolic blood pressure (SBP) (p.012) and diastolic blood pressure (DBP) (p.001) and correlated negatively with 25(OH)Vitamin-D (p.046). The multivariate analysis showed positive predictors of CAVI age (p.001), DBP (p.0001), ACR (p.008) and Klotho (p.017). Conclusion: In our DMT2 population, borderline and pathological CAVI is associated with increased ACR, elevated DBP and reduced 25(OH)Vitamin-D. Furthermore the alterations of FGF23, Sclerostin and Klotho, secondary to CKD, are an early sign of possible vascular damage. ACR, 25(OH)Vitamin-D and DBP can be modifiable risk factors for early vascular damage in DMT2